2015
DOI: 10.1016/j.joa.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cardiac resynchronization therapy for patients with New York Heart Association class IV non‐ambulatory heart failure

Abstract: CRT can be safely used in patients with NAHF and can improve long-term patient outcomes, especially in treatment responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Recently, several studies have shown that CRT did improve HF symptoms and survival rates of some IVD‐supported HF patients with FA‐IV status, although the overall outcomes were not as good as in HF patients with less disease severity; 1‐year survival ranged from 40% to 80% 6–12,17,26,27 . A beneficial effect of rescue CRT implantation for inotrope‐dependent HF patients was also demonstrated in a recently published meta‐analysis that incorporated 151 patients from eight related studies 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have shown that CRT did improve HF symptoms and survival rates of some IVD‐supported HF patients with FA‐IV status, although the overall outcomes were not as good as in HF patients with less disease severity; 1‐year survival ranged from 40% to 80% 6–12,17,26,27 . A beneficial effect of rescue CRT implantation for inotrope‐dependent HF patients was also demonstrated in a recently published meta‐analysis that incorporated 151 patients from eight related studies 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that predominantly included patients with ischaemic cardiomyopathy, the 1-year survival tended to decrease below 50%. 26 The 1-year survival rate was also affected by proportion of LBBB patients 7,9,10,12,19 ; it was only 40% when the proportion of LBBB patients was <50%, but it increased to 80% if LBBB patients numbered >70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the optimal hemodynamic response to the CRT depends not only on the site of stimulation of LV, but also on the optimization of A-V and V-V intervals 3 Some of the latest studies indicate positive effects of CRT and in the nonambulatory NYHA IV class, but more confirmation studies are needed. 4 The positioning of the electrode for LV as well as the number of electrodes is still often a compromise between theoretical, optimal pacing, and technical possibilities, with the suggestion of many authors that the optimal position and number of electrodes for stimulating the LK can be different from patients to patients. 5…”
Section: Discussionmentioning
confidence: 99%
“…However, current guidelines do not recommend CRT in non-ambulatory NYHA class IV HF patients [2,3] . Several small, retrospective studies of CRT implantation in inotrope-dependent HF patients have described high rates of successful implant, weaning from inotrope, clinical improvement, hospital discharge, and in some cases echocardiographic improvements following CRT [10][11][12][13][14][15][16][17] . To our knowledge, no previous studies or cases have specifically described CRT implant in ventilator-dependent HF patients.…”
Section: Discussionmentioning
confidence: 99%